Viable Systems Approach and Consumer Culture Theory: A Conceptual Framework. (1st November 2013) - Dominici, Gandolfo; Basile, Gianpaolo; Palumbo, Federica
<x xml:space="preserve">Abstract</x> The aim of this study is to depict the relational dynamics between the firm/brand and the individual/consumer or communities of consumers. To this aim we propose a conceptual framework, integrating the viable systems approach (VSA) with consumer culture theory (CCT), which considers the individual as an active co-maker of the product/brand ('prosumer'). The VSA view of the firm overcomes the limitations of CCT research, which is mainly focused on the individual, giving little consideration to the other actors in the context. Among the different approaches under the umbrella of viable systems we chose the VSA because of its emphasis on the analysis of the systemic external relations with the agents in the context, helping to underscore the marketing and social perspectives of CCT. Using a viable systemic perspective, the firm/brand and the individual/consumer can be conceived as viable systems embedded in a social-business context. Therefore, the consumption system can be considered as the momentum for the creation and maintenance of symbolic and cultural relationships between the firm/brand and the individual/consumer or communities of consumers (i.e. brand communities or subculture of consumption). These relationships are finalized to establish a common and consonant language in order to achieve a desired consonance level capable of enabling both the consumer and the firm/brand to co-evolve, maintain, and enhance their systemic viability.